Survey of Rice Diseases and Insect Pests in Northern Ghana (Journal of Science and Technology, 2016)
A survey was conducted in some rice-growing areas of northern Ghana during the rainy seasons of August-November; 1996-98 to determine the prevalence of rice pests with emphasis on diseases. Brown spot (Bipolaris oryzae) was identified as an emerging threat to rice production in the low-input cropping systems of the areas. Leaf blast (Pyricularia oryzae), narrow brown leaf spot (Cercospora janseana), leaf scald (Microdochium oryzae), glume discolouration (caused by several pathogenic fungi), false smut (Ustilaginoidea virens). stackburn (Alternaria padwickii) and sheath rot (Sarocladium oryzae) also occurred sometimes together on farmers' fields. Survey results based on enzyme-linked immunosorbent assay (ELISA) test has confirmed the presence of rice yellow mottle virus in Ghana. Seed sucking hugs, grasshoppers, caterpillars, termites, stem and seed borers, birds and non-parasitic weeds are potential constraints to rice production in the region. The weed species associated with rice production in the region are recorded in the text.